Simple Pendulum Experiment with Sound Assistance Using Arduino UNO for Students with Special Needs - Soni Prayogi; Fitria Silviana (International Journal of Educational Review, 2026)
In this paper, we propose a way to demonstrate the dependence of distance and time in a pendulum experiment to blind students. The periodic oscillations of the pendulum are translated, by the Arduino and the ultrasonic sensor, into periodic frequency variations across the speaker. The main advantage of this proposal is the possibility of blind students understanding gestures without having to touch them. Our results show that by converting the position range into the frequency range emitted by computer speakers and blind students can realize how the periodic pendulum movement occurs. we believe that the idea presented here can be used in other experimental demonstrations involving movement observations. Visually impaired students can use their hands in front of the sensor and move them to correlate the frequency with the distance and use it as a sound rule.